Entrepreneurial efforts by Bangladeshi immigrant women in New Zealand: a preliminary analysis / Rubaiyet Hasan Khan, Saida Parvin, Geetha Subramaniam - Parvin, Saida; Subramaniam, Geetha (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
This exploratory research investigates the entrepreneurial orientation among migrant Bangladeshi women in New Zealand. There have been many studies of higher degrees of entrepreneurship among the migrant communities in the western world but this research studies the role and trends among the Bangladeshi migrant women using a mixed method of study. The descriptive statistics show unique trends among this group of women entrepreneurs. The women face various challenges but they also deal with these challenges in their unique ways. The striking trend that was established was that the limited expectations are limiting the growth of the businesses among these group of entrepreneurs in New Zealand. The findings of this research may be of interest among various policy makers both at the national and international levels. This may also be of interest for researchers who study women empowerment concepts around the world.